A Precise Manufacturing Method of the Composite Structure-Similar Flutter Model. (3rd August 2014) - Yang, Rui; Sun, Shiyong; Qian, Wei; Guo, Dongming
Abstract : The composite structure-similar flutter model (ComSSM) not only shows higher structural efficiency but also provides convenience for the purpose of fabrication in the aerodynamic flutter model. The manufacturing process of ComSSM is different from conventional composites structures. The geometry parameters and nongeometry parameters of ComSSM need to be controlled cooperatively and precisely to obtain higher product quality. A method of precise manufacturing is developed based on the error calibration of nongeometry parameters. The accuracy of structural performance of ComSSM is ensured by reducing the manufacturing stiffness, controlling the error of mechanical performance, and calibrating the error of modal frequency.